Ultrafast Laser Direct-Writing of Self-Organized Microstructures in Ge-Sb-S Chalcogenide Glass - Torun, Gözden; Yadav, Anupama; Richardson, Kathleen A.; Bellouard, Yves (Frontiers in Physics, 2022)
The structuring of mid-IR materials, such as chalcogenide glass (ChG), at the micro and nano scales, is of high interest for the fabrication of photonic devices in general, and for spectroscopy applications in particular. One efficient method for producing regular patterns with sub-micron to micron length-scale is through self-organization processes occurring during femtosecond laser exposure. These processes occur in a broad set of materials, where such self-organized patterns can be found not only on the surface but also within the material volume. This study specifically investigates the case of chalcogenide glass (Ge23Sb7S70) exposed to femtosecond laser pulses, inducing pulse-to-pulse nanostructure formation that is correlated to the glass network structural evolution using Raman spectroscopy as well as morphological and elemental microscopy analysis.